Трансформационные изменения института семьи и брачных отношений в украинском обществе: гендерный анализ - Амджадин, Л. (Социология: теория, методы, маркетинг, 2007)
The article analyzes changes occurring in the sphere of marriage and family relation sin Ukrainian society, under the gender equality principles. The main attention is focused on the problems of gender asymmetry in marriage status and family descriptions of the Ukrainians, ideas of gender-role allocation of family responsibility for housework, attitudes towards child birth and care, etc. Referring both to statistical data and the results of sociological research, the author demonstrates that the institution of family as a comparatively stable social structure is still of the greatest importance in mass consciousness, although gender interests and expectations are not always justified.